Communication Management through the Waste Transport Information System (SIASAH) as Social Education towards Anti-Flood Southwest Papua - Manurung, Tagor; Manuhutu, Melda Agnes; Gaspersz, Sherly; Uktolseja, Lulu Jola (IJISTECH (International Journal of Information System and Technology), 2023)
Waste is a residue of daily human activities and is a natural process in solid form which is always found around human life. This condition is increasingly increasing as the population increases and causes more and more waste to be generated. Thus, it is a problem faced throughout the country or world, including in the Southwest Papua Province, Indonesia. The waste issue is a special concern for related parties, including the Environmental Protection and Management Service (DPPLH) and other sectors in Southwest Papua Province. This is done as an effort to prevent waste generation which can cause problems, one of which is flooding which has an impact on the social life of the people in the Southwest Papua region. Efforts to handle waste can be carried out through the use of technology as a medium of communication, outreach and information carried out by the government and the community through the Waste Transport Management Information System (SIASAH) platform at the Department. Therefore, this research can provide a thought contribution in the context of inter-line communication management related to efforts to build synergy to resolve the waste problem in Southwest Papua. The research approach used is a qualitative approach with a focus on information system development. Data collection efforts at the Sorong City Environmental Protection and Management Service (DPPLH), PT. Hendrina, the community, as well as several TPS and TPA in the Southwest Papua Province. Data obtained through observation and interviews. This system was created using the Rapid Application Development (RAD) Model with stages: 1) analysis and quick design, 2) prototype cycles (using the Balsamic mockup application 3 UML system modeling and the rational rise application then database design using MySQL), 3) testing using blackbox testing, and 4) implementation (using the SIASAH system that has been designed). The SIASAH system is here to become an educational platform for the public in providing information and improving government public services as well as providing digital-based information media support.